CONSEQUENCES OF HELICOBACTER PYLORI INFECTION - Kharchenko А.V.; Sherstyuk, O.A. (World of Medicine and Biology, 2018)
The consequences of influence of infection of Helicobacter are in-process shown pylori on the mucous membrane of stomach. Both histological methodologies and molecular-biological methodology (ISSR-PCR) are applied with ISSR-praimer S-2, with the structure (AGC) 6G. The changes of mucous membrane of stomach are analysed at H.˚pylori- the associated diseases: chronic ulcerous illness of duodenum, chronic ulcerous illness of stomach, ulcerous infiltration cancer of stomach. Histological in the mucous membrane of stomach found out dysplasias of three degrees of weight (D-1; D-ІІ; D-ІІІ). Genotype in a mucous membrane found out changes corresponding to microsatellite expansions that are the certificate of pre-cancer changes.